ASSESSMENT OF NURSES' KNOWLEDGE REGARDING SAFE PATIENT LIFTING AND HANDLING IN TERTIARY CARE HOSPITALS - ALI , MM; USMAN , A; ZUNAIRA, .; TASNEEM , SS; JABEEN , R (Biological and Clinical Sciences Research Journal, 2024)
Safe patient handling is a critical aspect of nursing care, aimed at preventing musculoskeletal injuries among healthcare providers and ensuring patient safety. In Pakistan, nurses face challenges such as limited access to handling equipment and inconsistent training, increasing their risk of injury and affecting patient care quality. Objective: This study assesses nurses' knowledge of safe patient lifting and handling and explores demographic and professional factors influencing this knowledge. Methods: A cross-sectional study was conducted among 200 nurses at the Department of Nursing, Superior University, Lahore, using a self-structured questionnaire. The questionnaire comprised demographic and professional information, alongside a 15-item knowledge assessment on safe patient handling. Correct responses were scored, and the mean score was calculated to categorize knowledge as "good" or "poor." Data analysis was conducted using SPSS version 22.0, employing descriptive statistics and chi-square tests for associations, with p≤0.05 considered significant. Results: Of the 200 nurses surveyed, 56.0% demonstrated good knowledge of safe patient handling, while 44.0% exhibited poor knowledge. Significant associations were found between knowledge levels and gender, qualifications, work position, and department. Females and those with advanced qualifications had higher knowledge levels, while age and work experience showed no significant influence. Nurses who had received training reported higher knowledge, though the difference was not statistically significant (p=0.16). Conclusion: The findings indicate that a significant proportion of nurses lack adequate knowledge of safe patient handling, highlighting the need for enhanced training and resources. Targeted interventions considering demographic and professional variations can bridge knowledge gaps and promote safer handling practices, reducing occupational risks and improving patient care quality. Further studies are recommended to explore institutional policies and cultural factors that may impact the adoption of safe patient-handling practices in Pakistan.